Perfume advertisements in the aspect of multimodal cohesion - Nikiforova , Yevhenia; Popivniak , Olena; Galitska , Elizaveta (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article deals with the specification of perfume advertisements, focusing on the interaction and cooperation of their semiotic modes, which are interrelated in cohesion both within the same semiotic mode and across different modes. The central objects of this investigation are perfume advertisements and their formal elements which create the whole semiotic structure. This structure has features of flexibility and functions as a hyper constituent or macro integrator, encompassing three constituents or modes that serve as micro integrators. Each constituent contains a sub-constituent or sub-mode which acts as a formal element, while these formal elements themselves comprise quasi-constituents or quasi-elements. The smallest units of the semiotic structure are hypo-constituents or hypo-elements. Within the verbal semiotic mode, some principal formal elements were identified, including functional blocks, subblock names and their lexical embodiments. The most developed functional block contains a naming complex with A1 brand (company) name, B2 individual name, C3 genitive (product) name, and D4 additional information. These names serve as bearers of lexical cohesion. Lexical cohesion in the verbal semiotic mode is realised through the mechanism of reiteration, including both repetition and synonyms and occurs between different functional blocks. Formal elements within this mode, such as a slogan, poster, logo, and wording, contribute to the process of lexical cohesion. The visual semiotic mode contains a set of formal elements such as composition, balance, and depth. It is described through a set of parameters, including plan, visual component, variable and constant details of the visual component. The advertisement depth is realised through front, middle and back plans with leading visual components being the perfume bottle, model, and scenery. The model receives the most detailed visual representation, including the model’s image, code of costume, and code of behaviour, which involves body language, pose, imitation of behaviour, and facial expression. Colour, as a media language, is firmly connected with the process of visualisation, manifesting across all visual components and providing visual repetition of colour or shade. Visual objects are repeated in different plans providing further cohesion between different plans. There is a definite correlation between verbal components-naming units and their visualisation, indicating further cohesion between verbal and visual semiotic modes. The olfactory semiotic mode includes two sub-modes or formal elements: a substantial formal element associated with perfume samples and a verbal formal element represented by descriptions of perfume smells. This mode uses the mechanisms of synaesthesia when the smell is represented through verbal description and optical visualisation, engaging visual, tactile, auditory, and gustatory receptions. However, this aspect of research warrants further investigation and deeper analysis.